ESCALES, Vanina. (2019) ¡Arroja la bomba! Salvadora Medina Onrubia y el feminismo anarco. Buenos Aires, Marea, 272 pp. - Tarducci, Mónica (Zona Franca, 2019)
ESCALES, Vanina. (2019) ¡Arroja la bomba! Salvadora Medina Onrubia y el feminismo anarco. Buenos Aires, Marea, 272 pp.